Expanding the Donor Pool: First Use of Hepatitis B Virus Nat Positive Solid Organ Allografts Into Seronegative Recipients. Issue 4 (October 2021) - Delman, Aaron M.; Turner, Kevin M.; Safdar, Kamran; Anwar, Nadeem; Silski, Latifa S.; Lee, Tiffany C.; Luckett, Keith; Cuffy, Madison C.; Quillin, Ralph C.; Schoech, Michael; Kaiser, Tiffany E.; Govil, Amit; et al.
Abstract : Objectives: The aim of this study was to assess the 1-year safety and effectiveness of HBV Nucleic Acid Test positive (HBV NAT+) allografts in seronegative kidney transplant (KT) and liver transplant (LT) recipients. Summary Background Data: Despite an ongoing organ shortage, the utilization of HBV NAT+ allografts into seronegative recipients has not been investigated. Methods: From January 2017 to October 2020, a prospective cohort study was conducted among consecutive KT and LT recipients at a single institution. Primary endpoints were post-transplant HBV viremia, graft and patient survival. Results: With median follow-up of 1-year, there were no HBV-related complications in the 89 HBV NAT+ recipients. Only 9 of 56 KTs (16.1%) and 9 of 33 LTs (27.3%) experienced post-transplant HBV viremia at a median of 185 (KT) and 269 (LT) days postoperatively. Overall, viremic episodes resolved to undetected HBV DNA after a median of 80 days of entecavir therapy in 16 of 18 recipients. Presently, 100% of KT recipients and 93.9% of LT recipients are HBV NAT− with median follow-up of 13 months, whereas 0 KT and 8 LT (24.2%) recipients are HBV surface antigen positive indicating chronic infection. KT and LT patient and allograft survival were not different between HBV NAT+ and HBV NAT− recipients ( P > 0.05), whereas HBV NAT+ KT recipients had decreased waitlist time and pretransplant duration on dialysis ( P < 0.01). Conclusions: This is the largest series describing the transplantation of HBV NAT+ kidney and liver allografts into HBV seronegative recipients without chronic HBV viremia or decreased 1-year patient and graft survival. Increasing the utilization of HBV NAT+ organs in nonviremic recipients can play a role in decreasing the national organ shortage. Abstract : Supplemental Digital Content is available in the text